2021
DOI: 10.1136/bmjopen-2021-050739
|View full text |Cite
|
Sign up to set email alerts
|

Combined association of obesity and other cardiometabolic diseases with severe COVID-19 outcomes: a nationwide cross-sectional study of 21 773 Brazilian adult and elderly inpatients

Abstract: ObjectivesTo investigate the combined association of obesity, diabetes mellitus (DM) and cardiovascular disease (CVD) with severe COVID-19 outcomes in adult and elderly inpatients.DesignCross-sectional study based on registry data from Brazil’s influenza surveillance system.SettingPublic and private hospitals across Brazil.ParticipantsEligible population included 21 942 inpatients aged ≥20 years with positive reverse transcription-PCR test for SARS-CoV-2 until 9 June 2020.Main outcome measuresSevere COVID-19 o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…Although young adults are considered to be at lower risk for hospitalization and disease severity, they became more prevalent when obese 5 . Furthermore, we found an inverse relationship between BMI and age that was also found in similar studies [9][10][11][12] . COVID-19 was not consistent with Brazilian epidemiology, where obesity is more prevalent in older adults 3 .…”
Section: Discussionsupporting
confidence: 90%
“…Although young adults are considered to be at lower risk for hospitalization and disease severity, they became more prevalent when obese 5 . Furthermore, we found an inverse relationship between BMI and age that was also found in similar studies [9][10][11][12] . COVID-19 was not consistent with Brazilian epidemiology, where obesity is more prevalent in older adults 3 .…”
Section: Discussionsupporting
confidence: 90%
“…[56][57][58] SARS-CoV-2 infection also predisposes patients to the incidence of many comorbidities, including low testosterone, erectile dysfunction (ED) and possibly an earlier onset or worsening of type 2 DM. 59 Cytokine storm can cause β-cell damage and apoptosis, hypoxia and abnormal remodeling of pancreatic cells. 60 Endothelial dysfunction is the ground for more severe progression of Covid-19…”
Section: Comorbidities Associated With Covid-19 Morbidity and Mortali...mentioning
confidence: 99%
“…Nie et al 43 Enikeev et al 44 Yang et al 66 SARS-CoV-2 can damage Sertoli cells (impairing spermatogenesis; ultimately leading to infertility) Enikeev et al 44 Yang et al 66 Achua et al 67 Ma et al 68 SARS-CoV-2 causes systemical endothelial dysfunction (leading to erectile dysfunction) Silva et al 59 Pons et al 61 Kresch et al 64 SARS-CoV-2 can cause cavernous endothelium damage (leading to erectile dysfunction) Kresch et al 64 SARS-CoV-2 causes orchitis Chen et al 65 Yang et al 66 Achua et al 67 Abbreviation: SARS-CoV-2, severe acute respiratory syndrome 2 coronavirus.…”
Section: Effect Of Testosterone Therapy On Covid-19 Morbidity and Mor...mentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis including more than 600.000 subjects showed that mortality changes across age categories, ranging from 9.5% (8073/ 85.358) in patients of 60-69 years old up to 29.6% (41.958/ 141.745) in those aged >80 years [14]. Table 1 and 2 summarize mortality rates extrapolated from clinical studies conducted in elderly patients with COVID-19 and factors associated with poor outcome [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Among biomarkers of infection, the increase in procalcitonin (PCT) values was associated with increased risk of hospital death in subjects > 75 years old, but not in younger ones J o u r n a l P r e -p r o o f [33].…”
Section: Clinical Presentation and Risk Of Deathmentioning
confidence: 99%